Critical Thinking Profiles of Junior High School Students in Solving Plane Geometry Problems Based on Cognitive Style and Gender - Men, Fulgensius Efrem; Gunur, Bedilius; Jundu, Ricardus; Raga, Polykarpus (Indonesian Journal of Science and Mathematics Education, 2020)
This study aimed to describe the students’ critical thinking processes in solving plane geometry problems based on cognitive styles and gender styles. This research used the descriptive qualitative method. The subjects of this study were four junior high school students selected based on differences in cognitive styles and gender styles. The instrument consisted of the main instruments are researchers and supporting instruments, namely problem-solving instruments, cognitive style instruments, and interview guidelines. The data were collected by means of tests and interviews. The results showed there is a significant difference in critical thinking based on students’ cognitive styles. Students with field independent cognitive style tend to go through critical thinking stages more fully than students with field dependent cognitive style. Besides that, gender differences also have an impact, although not as significant as the cognitive style.